2006
DOI: 10.1007/s00367-006-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of pteropods from the Western Arabian Sea sediment trap

Abstract: Sediment trap samples collected from the Western Arabian Sea yielded a rich assemblage of intact and non-living (opaque white) pteropod tests from a water depth of 919 m during January to September 1993. Nine species of pteropods were recorded, all (except one) displaying distinct seasonality in abundance, suggesting their response to changing hydrographical conditions influenced by the summer/winter monsoon cycle. Pteropod fluxes increased during the April--May peak of the summer monsoon, and reached maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Overall, the organic carbon export flux in the Arabian Sea during spring‐intermonsoon was found to be low compared to monsoon (Buesseler et al, ). Results of organic carbon measured from shallow sediment traps deployed at ~900 m water depth in the western Arabian Sea (16° 20′N 60° 18.8′E) also showed low organic carbon flux ~0.83 mmol m −2 d −1 (Mohan et al, ). A possible mechanism for such reduced export flux, though remineralization at this trap depth is significant, could be due to lack of diatom group of phytoplankton in this season, which could be able to ballast to deeper depth, caused by occurrence of nutrient poor oligotrophic conditions in the photic zone (Gauns et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the organic carbon export flux in the Arabian Sea during spring‐intermonsoon was found to be low compared to monsoon (Buesseler et al, ). Results of organic carbon measured from shallow sediment traps deployed at ~900 m water depth in the western Arabian Sea (16° 20′N 60° 18.8′E) also showed low organic carbon flux ~0.83 mmol m −2 d −1 (Mohan et al, ). A possible mechanism for such reduced export flux, though remineralization at this trap depth is significant, could be due to lack of diatom group of phytoplankton in this season, which could be able to ballast to deeper depth, caused by occurrence of nutrient poor oligotrophic conditions in the photic zone (Gauns et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of their sensitivity to ocean acidification, there has been a significant increase in research on this group over the past decades, including incubation experiments, studies on natural CO 2 gradients, and descriptions of the genetic variability within natural populations (see Manno et al, 2017). The impact of predicted future conditions on live specimens has been assessed using wide variety of parameters, including calcification (Comeau et al, 2009(Comeau et al, , 2010Maas et al, 2018;Moya et al, 2016), shell degradation (Bednaršek et al, 2012b;Bergan et al, 2017;Lischka and Riebesell, 2012), metabolic rates (Lischka and Riebesell, 2017;Maas et al, 2011;Seibel et al, 2012), respiration (Comeau et al, 2010;Maas et al, 2018;Moya et al, 2016), and gene expression patterns (Koh et al, 2015;Maas et al, 2015Maas et al, , 2018Moya et al, 2016;Thabet et al, 2017). Generally, previous studies have found that as the aragonite saturation state decreases, pteropod calcification rates decrease (Comeau et al, 2010(Comeau et al, , 2009Lischka and Riebesell, 2012).…”
Section: Understanding Natural Pteropod Variabilitymentioning
confidence: 99%
“…Pteropod shell condition has been used to visually assess the extent of shell dissolution in both modern and fossil samples (Gerhardt et al, 2000;Gerhardt & Henrich, 2001). In the modern ocean, the condition of pteropod shells in sediment traps have been used to monitor carbonate chemistry (Meinecke & Wefer, 1990;Mohan et al, 2006), with the notion that shell dissolution is indicative of aragonite undersaturated waters between the sea surface and the depth of the sediment trap (Almogi-Labin et al, 1986;Gerhardt et al, 2000). In the fossil record, shell condition has been used to assess the impact of dissolution on the growth of living pteropods and their subsequent alteration during burial.…”
Section: Introductionmentioning
confidence: 99%